TOWARDS AN EFFECTIVE TEACHERS’ PROFESSIONAL LEARNING - Hefnawi, Ayman (PEOPLE: International Journal of Social Sciences, 2017)
Teachers’ professional development (PD) is an essential tool in helping them meet the change requirements imposed by the continuing school improvement plans. In order to evaluate the quality and impact of the provided PD programmes, the ways teachers perceive and approach the provided PD programmes are important factors to investigate. Thus, this paper focuses on the factors that might influence the ways teachers perceive and approach the provided PD activities. In Particular, factors related to the school learning culture were the focus of this paper. The reason is that the features of school learning culture inevitably influence the ways teachers perceive and approach their professional learning in many different ways. The research that was reviewed in this paper suggested strategies for school leaders to build and sustain learning cultures that facilitate learning at all levels in schools. Additionally, the discussed literature proposed a potential effective strategy for planning and evaluating the impact of PD programmes that would increase the effectiveness of teacher PD programmes.